Flavonoids and biphenylneolignans with anti-inflammatory activity from the stems of Millettia griffithii. Issue 18 (15th September 2016) - Tang, Huan; Pei, He-Ying; Wang, Tai-Jin; Chen, Kai; Wu, Bo; Yang, Qiu-Nan; Zhang, Qiang; Yang, Jian-Hong; Wang, Xiao-Yan; Tang, Ming-Hai; Peng, Ai-Hua; Ye, Hao-Yu; et al.
Graphical abstract: Highlights: Sixteen compounds were isolated from the stems of Millettia griffithii . Six new compounds, including five flavonoids and a biphenylneolignan. Griffinone B (2 ) displayed potent anti-inflammatory activity (IC50 2.1 μM). Western blot, PCR assay and modeling studies of griffinone B (2 ) was performed. Abstract: Five new flavonoids, griffinones A–E (1 –5 ), a new biphenylneolignan, griffilignan A (6 ) and ten known compounds were isolated from the n -hexane and EtOAc extracts of Millettia griffithii . The structures of the new compounds were determined by 1D and 2D NMR, and by HRMS. The anti-inflammatory activity of the isolated compounds was evaluated on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW 264.7 cells. Among the isolated compounds, compounds1, 2 and14 showed significant anti-inflammatory activity with IC50 values of 20.4, 2.1 and 35.7 μM, respectively and no obvious toxicities were observed at 100 μM. Western blot and PCR assay further showed that inhibition of nitric oxide production by compound2 was associated with suppression of iNOS expression. Modeling studies suggested that the amino group, phenyl ring as well as the isopentenyl tails of compound2 could help bind to iNOs.